2017
DOI: 10.1158/0008-5472.can-16-3563
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Analysis of Oncogenic Gene Fusions in Primary Colon Cancer

Abstract: Genomic rearrangements that give rise to oncogenic gene fusions can offer actionable targets for cancer therapy. Here we present a systematic analysis of oncogenic gene fusions among a clinically well-characterized, prospectively collected set of 278 primary colon cancers spanning diverse tumor stages and clinical outcomes. Gene fusions and somatic genetic variations were identified in fresh frozen clinical specimens by Illumina RNA-sequencing, the STAR fusion gene detection pipeline, and GATK RNA-seq variant … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
85
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 85 publications
(91 citation statements)
references
References 46 publications
4
85
2
Order By: Relevance
“…In colorectal cancer, the reported prevalence of these fusions is similar. When the results of three previous studies were combined, PTPRK – RSPO3 and EIF3E – RSPO2 were detected in six (1.4%) and five (1.2%) lesions, respectively, among a total of 421 colorectal cancers . In contrast, EIF3E – RSPO2 is far less common than PTPRK – RSPO3 in TSAs, as shown in the present study .…”
Section: Discussionsupporting
confidence: 64%
See 2 more Smart Citations
“…In colorectal cancer, the reported prevalence of these fusions is similar. When the results of three previous studies were combined, PTPRK – RSPO3 and EIF3E – RSPO2 were detected in six (1.4%) and five (1.2%) lesions, respectively, among a total of 421 colorectal cancers . In contrast, EIF3E – RSPO2 is far less common than PTPRK – RSPO3 in TSAs, as shown in the present study .…”
Section: Discussionsupporting
confidence: 64%
“…In addition, we identified EIF3E – RSPO2 and PIEZO1 – RSPO2 fusions in three and one TSAs, respectively. Although EIF3E – RSPO2 has been reported as a recurrent genetic alteration in colorectal cancer, this fusion had not previously been found in any colorectal polyps. We formerly postulated the presence of a rare type of colorectal cancer precursor harbouring this fusion, because our previous studies involving a total of > 300 different types of colorectal polyp, including 129 TSAs, failed to identify EIF3E – RSPO2 in any of the lesions .…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…Recently, a novel USP9X‐ERAS promoter swap fusion was identified in a single colorectal cancer case, leading to high expression of ERAS, a RAS‐family member that enhances PI3K/AKT pathway activation . Overexpression was driven by the fusion of ERAS with the 5′UTR and promoter sequence of USP9X , which is highly expressed in colon .…”
Section: Discussionmentioning
confidence: 99%
“…34 Overexpression was driven by the fusion of ERAS with the 5 0 UTR and promoter sequence of USP9X, which is highly expressed in colon. 34 MPseq revealed that the novel promoter swap fusion was formed through a localized chromothripsis event on chromosome X including the region covered by USP9X and ERAS. 34 This case suggests that the ubiquitously expressed USP9X gene may be a recurrent translocation partner in other tumor types.…”
Section: Case Reportmentioning
confidence: 99%